Peluang dan Tantangan Dalam Mempersiapkan Desa Wisata Rintisan Menuju Pariwisata Berkelanjutan - Yuviani Kusumawardhani; Taufik Kurniawan; Dina Hariani (Bogor Hospitality Journal, 2025)
SDGs as a global agenda in development in various sectors is still a difficult phenomenon to do, especially in developing countries. Indonesia as a developing country is still experiencing obstacles, especially in the tourism sector. The Indonesian government continues to strive to develop sustainable tourism, one of which is through sustainable certification of tourist villages in Indonesia. Bogor Regency, in West Java Province, is one of the certified tourist villages. However, among other provinces, West Java province only has one certified tourist village located in Bogor District. Other provinces have at least two certified tourist villages.The slow development of tourism villages in Bogor Regency is partly due to the lack of support from stakeholders. Based on this, this study aims to examine more deeply the challenges and opportunities in shaping sustainable tourism villages in Bogor District. This research is exploratory in nature, and the researcher used a qualitative approach based on phenomenology to explore in-depth information related to challenges and opportunities from 11 resource persons who are stakeholders of tourist villages in Bogor Regency. Finally, this research provides an overview of the challenges and opportunities in developing tourism villages in Bogor Regency, so that it will be easier to take preventive action to develop tourism villages towards the principle of sustainability.